Navigation in Space by X-ray Pulsars - Emadzadeh, Amir Abbas; Speyer, Jason Lee.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
This monograph on different aspects of utilizing X-ray pulsars for navigation of spacecraft in space contains two unique features. First, it provides a solid mathematical formulation for the absolute and relative navigation problems based on use of X-ray pulsar measurements. Second, it presents a comprehensive framework for signal processing techniques needed to obtain the navigation solution. Navigation in Space by X-ray Pulsars opens with background knowledge on pulsars and a review of the literature on pulsar-based navigation. It then presents the navigation problem and develops the X-ray pulsar signal models, formulating and analyzing the pulse delay estimation problem through these models. It proposes different pulse delay estimators and, using these estimators, provides a recursive algorithm to obtain the navigation solution. Closing with suggestions for future work in the field, this monograph is aimed at students, researchers and industry practitioners involved with new space navigation techniques.
1 Prologue -- 1.1 Current Spacecraft Navigation Systems -- 1.2 Pulsar-Based Relative Navigation -- 1.2.1 Why Relative Navigation? Why Celestial-Based Systems?- 1.2.2 Pulsars -- 1.2.3 Why Use X-ray Pulsars for Navigation?- 1.2.4 History of Pulsar-Based Navigation -- 1.3 Proposed Navigation System Structure -- 1.4 Thesis Outline -- 2 Signal Modeling -- 2.1 X-ray Detectors -- 2.2 X-ray Pulsar Signal -- 2.2.1 Constant-Frequency Model -- 2.2.2 Time-Dependent-Frequency Model -- 2.3 Discussion -- 2.4 Epoch Folding -- 2.4.1 Effect of Velocity Errors -- 2.5 Generating Photon TOAs -- 2.6 Simulation -- 3 Pulse Delay Estimation -- 3.1 Pulse Delay Estimation -- 3.2 The Cramér-Rao Lower Bound (CRLB) -- 3.3 Discussion -- 3.4 Simulation -- 4 Pulse Delay Estimation Using Epoch Folding -- 4.1 Cross Correlation Technique -- 4.2 Nonlinear Least Squares Technique -- 4.3 Simulation -- 5 Pulse Delay Estimation via Direct Use of TOAs -- 5.1 Maximum-Likelihood Estimator (MLE) -- 5.2 Numerical Determination of the MLE -- 5.3 Simulation -- 6 Recursive Position Estimation -- 6.1 System Dynamics -- 6.2 Measurements -- 6.3 Discrete-Time Estimation Process -- 6.4 Discussion -- 6.5 Simulation -- 7 Epilogue References.
Keywords: Engineering; Astronautics; Engineering; Aerospace Technology and Astronautics; Signal, Image and Speech Processing; Control